Analysis of the Tomato spotted wilt virus Ambisense S RNA-Encoded Hairpin Structure in Translation - Geerts-Dimitriadou, Christina; Lu, Yun-Yueh; Geertsema, Corinne; Goldbach, Rob; Kormelink, Richard (PLOS ONE, 2012)
Background The intergenic region (IR) of ambisense RNA segments from animal- and plant-infecting (-)RNA viruses functions as a bidirectional transcription terminator. The IR sequence of the Tomato spotted wilt virus (TSWV) ambisense S RNA contains stretches that are highly rich in A-residues and U-residues and is predicted to fold into a stable hairpin structure. The presence of this hairpin structure sequence in the 3′ untranslated region (UTR) of TSWV mRNAs implies a possible role in translation. Methodology/Principal Findings To analyse the role of the predicted hairpin structure in translation, various Renilla luciferase constructs containing modified 3′ and/or 5′ UTR sequences of the TSWV S RNA encoded nucleocapsid (N) gene were analyzed for expression. While good luciferase expression levels were obtained from constructs containing the 5′ UTR and the 3′ UTR, luciferase expression was lost when the hairpin structure sequence was removed from the 3′ UTR. Constructs that only lacked the 5′ UTR, still rendered good expression levels. When in addition the entire 3′ UTR was exchanged for that of the S RNA encoded non-structural (NSs) gene transcript, containing the complementary hairpin folding sequence, the loss of luciferase expression could only be recovered by providing the 5′ UTR sequence of the NSs transcript. Luciferase activity remained unaltered when the hairpin structure sequence was swapped for the analogous one from Tomato yellow ring virus, another distinct tospovirus. The addition of N and NSs proteins further increased luciferase expression levels from hairpin structure containing constructs. Conclusions/Significance The results suggest a role for the predicted hairpin structure in translation in concert with the viral N and NSs proteins. The presence of stretches highly rich in A-residues does not rule out a concerted action with a poly(A)-tail-binding protein. A common transcription termination and translation strategy for plant- and animal-infecting ambisense RNA viruses is being discussed.